A signal-on electrochemiluminescence immunosensor for A2780 cell detection based on the excellent catalytic performance of Co2+ doped TiO2 nanodisks. Issue 1 (4th November 2022) - Zhang, Shupei; Huang, Yitian; Chen, Yanjie; Yan, Shanshan; Dai, Hong; Zhao, Junhua
Abstract : A selective and sensitive A2780 cell analysis platform was established. Abstract : This study aimed at fabricating a new analysis platform for ovarian cancer cells based on metal organic frameworks derived Co 2+ doped TiO2 nanodisk (Co-TiO2 ND) mediated cathodic electrochemiluminescence (ECL) of Ru(bpy)3 2+ . Concretely, Co-TiO2 NDs were synthesized by applying a facile strategy and were revealed to possess a mesoporous structure, high surface area, good stability and conductivity, particularly excellent catalytic performance for the oxygen reduction reaction (ORR). Therefore, Co-TiO2 NDs did not only serve as a promising scaffold to carry amounts of folic acid (FA) for the subsequent immuno-identification reaction but were also utilized to catalyze the ORR reaction and produce substantial ˙OH to improve the ECL signals of Ru(bpy)3 2+ . Moreover, helical carbon nanotubes (HCNTs) with strong mechanical strength, excellent electronic transport properties and abundant active sites have emerged as a fascinating sensing matrix for fixing a high quantity of biomolecules (AbCA125 ). Then, the target cells A2780 were captured by the specific recognition between AbCA125 and CA125 on A2780 cells, and the FA functionalized probe was attached through the recognition of the FA acceptor on the surface of the cells, which established a "signal on" ECL cytosensor for A2780 detection with a linear range from 2.6 × 10 2 to 2.6 × 10 6 cells per mL. Promisingly, the successful application of Co-TiO2 NDs opens up a new avenue for developing excellent ECL sensors and broadens the application of metal organic frameworks.